First system-level evaluation of Italian National Parks management effectiveness for nature conservation - Marco Galaverni (Discover Conservation)
Abstract National Parks are usually considered as the most organized and effective forms of protection of natural territories, but formal estimates of their efficacy in protecting biodiversity do provide sometimes-contrasting results. In this study, we investigated the effectiveness of all the Italian National Parks (n = 23) through a RAPPAM-like methodology (Rapid Assessment and Prioritization of Protected Areas Management), with questionnaires submitted to Park directors, presidents or other relevant staff, with the aim to understand the strength and weaknesses of the National Parks and of the Italian park system in effectively conserve biodiversity and other values. Results suggest that the lack of basic management tools (e.g. Park Plans), poor areas designation (in terms of size and shape) and under staffing (especially for technical personnel such as biologists and veterinarians) are the main factors affecting the effectiveness of Italian National Parks. Coupled with external pressures (mainly from tourism, climate change, and wildfires) and future threats (mainly climate change) and with a reportedly poor coordination of the protected areas system, these weaknesses can hinder the targets recently set by the Convention on Biological Diversity and by the European Biodiversity Strategy to reach effectively-managed and well-connected protected areas that cover at least 30% of land and sea by 2030.